INFLUENCE OF THE RESERVOIR SEDIMENTATION ON THE DAM OPERATION – A STUDY OF ASWAN HIGH DAM IN EGYPT - Amir M. Mobasher (JES: Journal of Engineering Sciences, 2020)
Reservoirs are an important source of water supply, provide hydropower, reduce the deficiency influences, and provide flood protection. Due to the dam structure and reservoir founding, the releases from the dam has become more restrained and the hanging sediment concentricity summits have been decreased considerably and accumulated upstream the dam. Sediment siltation has increasingly reduced the efficiency of reservoir functionality throughout the years by declining the storage capability. Determining the reservoir sedimentation influence on the dam operation is important to holding current operation and preparing for future polices. The existing paper deals with the review and assessment of the reservoir sedimentation effect on operation of Aswan High Dam (AHD) in Egypt. A new simulation model was developed and calibrated for Aswan High Dam Reservoir (AHDR) to evaluate the reservoir sedimentation effects on the factors affecting the operation of the dam. These factors are Toshka spillway outflows, upstream water levels of AHD, dam safety, withdraw from the reservoir, the losses due to the evaporation and the hydropower generation from AHD. The results of the study displayed that the factors affecting the operation of AHD were affected due to presence of these deposits in AHDR. Therefore, the reservoir sedimentation effect should be considered to implement or develop of simulation models for AHDR.